Epêntese consonantal em contexto de juntura morfêmica : considerações sobre o sufixo -ada - Pires, Caroline de Castro (2016)
This study is a morphophonological and etymology analysis of words from a dictionary (HOUAISS, 2009) with the termination -ada, more specifically, we observe the morphemic context (base + suffix) of word derived from nominal basis, with and without consonant insertion and we try to find generalizations. It should be noted, especially, that this dissertation is meant to discuss words with nominal bases that have consonantal epenthesis ─ a mechanism used to solve structural problems of syllabic character. For data analysis, methodologically, the sample was divided into three major groups: (i) words derived from nominal basis (divided into thematic and athematic words); (Ii) words derived from verbal basis; and (iii) words with the termination -ada not suffixal (composed of vernacular formations and loans). From this work, it was found that words derived from thematic and athematic bases (it refers to a regular insertion in Portuguese) behave differently: (i) words with athematic bases, insert /z/, consonant less invasive, because only solves the syllabic character problem (cf. pá + -ada > pazada); (ii) words with thematic bases insert /r/ and neutralize the VT of base word in favor of the vowel /a/ (cf. bicho + -ada > bicharada). Moreover, the consonant epenthesis were characterized on the basis of texts used as theoretical foundation and the analysis of data which allowed the identification of more favorable context for the consonant inserts in PB: the athematic base words (20.5% against 2.6% of the thematic base words). Within of the athematic, the most favorable context is the words ending in a vowel candidate of accent (66.6%). Was highlighted also the possible reasons for the PB system select other consonants, different from /z/ and /r/, based on our data, like the fact there are already similar forms in the language with different semantics specification (cf. livroxada ~ livrada), the issue of variation (cf. bambu < bambucada ~ bambuzal ~ bambuØal), and cases of etymological trace (cf. paulada). Finally, we highlighted the need to carry out tests with speakers to observe the productivity of /z/ and /r/ in the PB system, the hypothesis is that /r/ is more crystallized in the language, and /z/ it is consonant with regular insertion force, i.e., probably it is the consonant more applied by native speakers of PB.